Development of an effective one-step double-antigen sandwich ELISA based on p72 to detect antibodies against African swine fever virus - Wang, Lei; Li, Duan; Liu, Yanlin; Zhang, Leyi; Peng, Guoliang; Xu, Zheng; Jia, Hong; Song, Changxu (Frontiers in Veterinary Science, 2023)
African swine fever (ASF), caused by ASF virus (ASFV), is a highly contagious and lethal disease of domestic pigs leading to tremendous economic losses. As there are no vaccines and drugs available. An effective diagnosis to eliminate ASFV-infected pigs is a crucial strategy to prevent and control ASF. To this end, ASFV capsid protein p72 was expressed using Chinese hamster ovary (CHO) cells and subsequently conjugated with horseradish peroxidase (HRP) to develop a one-step double-antigen sandwich enzyme-linked immunosorbent assay (one-step DAgS-ELISA). The performance of this ELISA for detecting ASFV antibodies was evaluated. Overall, a diagnostic sensitivity of 97.96% and specificity of 98.96% was achieved when the cutoff value was set to 0.25. No cross-reaction with healthy pig serum and other swine viruses was observed. The coefficients of variation of the intra-assay and inter-assay were both <10%. Importantly, this ELISA could detect antibodies in standard serum with 12,800-fold dilution, and seroconversion started from the 7th day post-inoculation (dpi), showing excellent analytical sensitivity and great utility. Furthermore, compared to the commercial kit, this ELISA had a good agreement and significantly shorter operation time. Collectively, a novel one-step DAgS-ELISA for detecting antibodies against ASFV is developed, which will be reliable and convenient to monitor ASFV infection.